Clinical Importance of Jaw Elevation during Conscious Sedation in Pediatric Patients - Verma, Gaurav (International Journal of Dental Research, 2013)
Pediatric patients differ from adult in behavioral aspects. The reason for this is that, they are in developing stage and may not have the ability to understand the things similar to adults. Therefore, to perform surgical procedures in pediatric patients some form of behavioral modification techniques along with pharmacological measures may be required. Conscious sedation is one of the commonly employed techniques in this regard. Respiratory depression or arrest is a life threatening complication which may occur during conscious sedation. The purpose of this note is to draw attention of anesthesiologist toward importance of jaw elevation during conscious sedation in pediatric patients and to initiate future studies to evaluate the efficacy of newer jaw elevation device in achieving this goal.